Oak symbolism in the light of genomics - Leroy, Thibault (New Phytol, 2019)
Throughout the Northern Hemisphere, human societies, political systems and religions have appropriated oaks in symbolic representations. In this review, we explore the possible associations between recent genetic and genomic findings and the symbolic representations of oaks. We first consider the ways in which evolutionary history during the Holocene has tightened links between humans and oaks in Europe, and how this may have led to symbolic representations. We then show how recent findings concerning the structure and evolution of the oak genome have provided additional knowledge about symbolic representations, such as longevity, cohesiveness and robustness.